A Semiotic Analysis Of Emoticon Symbols on Whatsapp Messenger In Students’ Chat Activies - Yoandini Hanafi; Muhammad Basri D; Hadijah Hadijah (Tamaddun Life, 2021)
The purpose of this study was to find out more about the meaning of semiotic and the use of emoticon symbols and how students view the use of emoticon symbols on WhatsApp messenger. This study uses a qualitative method. To collect data and determine research subjects, the authors used a questionnaire and observation as research instruments. The results of this study prove that most students mean the meaning of each emoticon symbol on WhatsApp and often use emoticon symbols in chat activities on WhatsApp messenger. They often express feelings and expressions through the symbol emoticon. Two main points are discussed in this thesis. First, the semiotic meaning and use of emoticon symbols, and the second, students' views on the use of emoticon symbols on WhatsApp messenger.